A lipid‐managing program maintains a stout Spitzenkörper. Issue 1 (26th May 2015) - Peñalva, Miguel A.
Summary The Spitzenkörper (SPK) is an accumulation of vesicles interleaved with actin microfilaments present at the cytosolic side of the apical plasma membrane (PM) of hyphal tips of many species of filamentous fungi. The physiological role of the SPK has captivated fungal biologists over the years, but only very recently this 'organelle' is starting to be understood in the molecular terminology used for cell biological models. One aspect that has received little attention is the role of cellular membrane asymmetry in the organization of membrane traffic, in particular in the genetic and cell biological model Aspergillus nidulans. The paper by Schultzhaus et al. (2015) in this issue breaks the ice, providing original insight that may foster research in phospholipid composition in the context of intracellular traffic and the organization of the SPK. Notably, it shows that like the stout Neurospora crassa SPK, the much slimmer one of A. nidulans, appears to be formed by different strata, altogether suggesting that the SPK might be a mosaic of exocytic carriers with different functional specializations, and a major sorting hub for intracellular membranes.